Hubungan Tingkat Stress dengan Perilaku Merokok pada Remaja - Amelia Ermi Juwita; Murniati Muchtar; Herwati Nurmin; Wira H Nidia; Indri Ramadini; Metri Lidya (Jurusan Keperawatan Mandiri Poltekkes Kemenkes Padang, 2025)
Smoking behavior causes various diseases such as cancer, heart and lung disease. The nicotine content in cigarettes affects dopamine in the brain, causing addicted and affects the sympathetic nerves so that smoking behavior is felt to relieve stress. Currently smoking behavior is not only found in adults but is also often found in adolescence, around 35.5% are male smokers in their adolescence. The purpose of the research is to determine the relationship between stress levels and smoking behavior in class XI adolescent students at SMK Negeri 1 Padang in 2024. Quantitative research type, analytical descriptive design, cross sectional study approach. The population was all male students in class XI totaling 413, sample of 78 students, selected by simple random sampling. Instruments a Stress level questionnaire and smoking behavior. Data analysis Chi-square test. The results show almost half of the adolescent students were in the moderate smoking behavior (44,9%) with the moderate stress level (46.2%). There is a relationship between stress levels and smoking behavior in adolescent with a p-value=0.000 (<0.05).